Factors related to sleep in family caregivers of people with dementia: A systematic review - Sonoko Kabaya; Chieko Greiner; I Gede Juanamasta; Yupin Aungsuroch (Jurnal Keperawatan Padjadjaran, 2023)
Background: Family caregivers (FCGs) face many problems when taking care of people with dementia. Purpose: This study wanted to explore the factors related to FCGs’ sleep in people with dementia. Methods: The study used a systematic review approach based on PRISMA. The study focused on FCGs for people with dementia in the home setting. A narrative synthesis was employed. Results: The result showed that the sleep problem and severity of a patient with dementia have an essential role in their state. Those indirectly impact the FCGs’ condition. The majority of the study’s sleep problems were related to physical fatigue that influenced the FCGs’ distress. Coping mechanisms have an essential role in the caregiver situation. A maladaptive coping mechanism would increase the stress of the caregiver and lead to a sleep problem. Conclusion: The consequences of those are burden and depression. Therefore, FCGs should be supported by families, friends, and healthcare workers. Community online groups of the FCGs might be helpful to support each other.